Using a Visual Structured Criterion for the Analysis of Alternating-Treatment Designs. Issue 1 (January 2019) - Lanovaz, Marc J.; Cardinal, Patrick; Francis, Mary
Although visual inspection remains common in the analysis of single-case designs, the lack of agreement between raters is an issue that may seriously compromise its validity. Thus, the purpose of our study was to develop and examine the properties of a simple structured criterion to supplement the visual analysis of alternating-treatment designs. To this end, we generated simulated data sets with varying number of points, number of conditions, effect sizes, and autocorrelations, and then measured Type I error rates and power produced by the visual structured criterion (VSC) and permutation analyses. We also validated the results for Type I error rates using nonsimulated data. Overall, our results indicate that using the VSC as a supplement for the analysis of systematically alternating-treatment designs with at least five points per condition generally provides adequate control over Type I error rates and sufficient power to detect most behavior changes.